Thermomechanical analysis of thermoplastic composite prepregs using bias-extension test. (May 2014) - Wang, Peng; Hamila, Nahiène; Pineau, Pierre; Boisse, Philippe
The results of in-plane shear tests performed on 5-hardness satin woven carbon/polyphenylene sulphide and polyetheretherketone thermoplastic prepregs are described in this article. The experimental analyses are based on bias-extension tests performed in an environmental chamber. The results are given for different temperatures on both sides of the melting point. This range of temperature is that of the part during a thermoforming process. The effect of displacement rate is also investigated. The results are given both as load versus displacement curves and as shear-moment versus shear-angle curves. The latter data can be directly used in a thermoforming simulation code. It is shown on a forming simulation example that the temperature and the related change of the shear behaviour have strong consequences on the final composite part. In particular, wrinkles can develop when the process temperature is too low.